Fatores associados ao óbito de pacientes oncopediátricos no Brasil: uma análise a partir dos registros hospitalares de câncer - Moura, Ana Beatriz Rodrigues (2023)
Cancer is the main cause of death from disease in the age group between one and nineteen years old in Brazil. The need for a greater understanding of death records from pediatric cancer in the country is highlighted in order to optimize health strategies in this segment. The objective of this study was to evaluate the possible factors associated with the mortality of children and adolescents due to cancer in Brazil. This is a cross-sectional study with secondary data through the analysis of cancer electronic health records (EHRs), whose population consisted of patients aged 0 to 19 years, of both sexes, diagnosed with malignant neoplasms, in the period from 2000 to 2019. Of the total of 46,526 cases, those that exceeded 365 days to start treatment after the date of diagnosis and those that presented loss of information regarding the variables of interest were excluded. After applying the eligibility criteria, 31,954 cases were descriptively and inferentially analyzed using logistic regressions (α=5%). A statistical model was designed for each of the 15 histological types analyzed. Death cases accounted for 22.8% (n=7,288) of the sample. There was a higher prevalence of death in males (56.97%), aged 0 to 4 years (32.17%), self-declared as brown (53.89%), living in the Northeast region (38 .57%), with solid tumors (53.13%), referred by the Sistema Único de Saúde (SUS) [Brazilian public health system] (88.64%), treated at the Oncology Pediatrics clinic (44.16%) and histological type lymphoblastic leukemia or lymphoid (28.96%). Patients with lymphoblastic or lymphoid leukemia were less likely to progress to death when not referred by the SUS (OR=0.93) and residing in the Northeast (OR=0.96), Midwest (OR=0.90) regions. and South of the country (OR=0.91), while their chances of death increased in the age groups of 10 to 14 years (OR=1.09) and 15 to 19 years (OR=1.21), when treated in clinics Clinical Oncology (OR=1.06) and Clinical Hematology (OR=1.03) and with more than one tumor (OR=1.15). Children and teenagers with nephroblastoma were less likely to die when not referred by the SUS (OR=0.90) and residents of the southern region of the country (OR=0.92), and their chances increased when they had more than one tumor (OR=1.31). Patients with Ewing's sarcoma had a lower chance of death when treated at the Radiotherapy clinic (OR = 0.69) and higher chances in the age groups 10 to 14 years (OR=1.16) and 15 to 19 years (OR= 1.17), while patients with germ cell tumors, trophoblastic tumors and gonad neoplasms were less likely when living in the southern region of the country (OR=0.91) and when treated at the radiotherapy clinic (OR=0.94). The chances of death were lower for patients with malignant glioma (OR=0.84) and astrocytoma (OR=0.86) when not referred by the SUS and for those with neuroblastoma (OR=0.86), retinoblastoma (OR= 0.78), when residing in the southern region of the country. Furthermore, it was observed that individuals with medulloblastoma with more than one tumor were more likely to die (OR=1.77). Age group, region of residence and origin of referral were the factors most frequently associated with mortality of children and adolescents from cancer in Brazil, with important variations according to the histological types of neoplasms.